Tindak Tutur Asertif dan Ekspresif pada Video Ekosistem Pendidikan Merdeka dalam Belajar - Intan Wulan Sari (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2022)
Speech is used by a speaker to convey purpose and purpose to the speech partner, through speech and the accompanying context. The goal of this time, therefore, is to identify a single act of assupportive and expressive speech in the appeal of najelaa shihab in a large youtube video entitled